Acupuncture combined with opioids for cancer pain: a pilot pragmatic randomized controlled trial. Issue 2 (April 2022) - He, Yihan; Zhang, Haibo; Li, Yifang; Long, Shunqin; Xiao, Shujing; May, Brian H; Lin Zhang, Anthony; Guo, Xinfeng; Xue, Charlie Changli; Lu, Chuanjian
Objective: Given the existing evidence for the analgesic effect of acupuncture, the current study aimed to assess whether acupuncture could be feasible and manageable as an adjunctive therapy for cancer pain in a real-world hospital setting. Methods: Thirty patients in an Oncology department with moderate or severe pain were recruited and randomized to an adjunctive acupuncture group or control group, who received pharmacotherapy for pain management without acupuncture. The duration of the treatment course was 1 week with a 2-week follow-up. In total, four acupuncture sessions were administered, on days 1/2/4/6 of the trial. Pain intensity was measured using a numerical rating scale (NRS) and the daily opioid dose was recorded. Results: The overall trends favored acupuncture for both pain intensity and daily opioid consumption. The proportion of participants experiencing at least a 2-point reduction in the NRS at the end of the treatment was 93% (n = 14/15) for the acupuncture group and 57% (n = 8/14) for the control group (risk difference (RD) 36.1%, 95% confidence interval (CI) [7.4%–65.0%]; relative risk (RR) 1.63, 95% CI [1.02–2.62]; p = 0.04). There were no serious adverse events and no dropouts during the treatment. Conclusion: This pilot study showed that adding acupuncture to routine analgesia for patients with cancer pain was feasible and acceptable to patients. The clinical effects of adding acupuncture as an adjunctive therapy need to be further evaluated. Clinical trial registration number: ChiCTR1800017023 (Chinese Clinical Trial Registry)